Serum TSH levels are associated with cardiovascular risk factors in overweight and obese adolescents - Luciana Lopes de Souza; Erika Paniago Guedes; Patrícia Fátima dos Santos Teixeira; Rodrigo Oliveira Moreira; Amelio Fernando Godoy-Matos; Mario Vaisman (Elsevier, 2016)
Objective: To investigate the relationship between serum thyrotropin (TSH), insulin resistance (IR), and cardiovascular risk factors (CRF) in a sample of overweight and obese Brazilian adolescents. Methods: A retrospective, longitudinal analysis of 199 overweight and obese pubescent adolescents was performed. The TSH and free T4 (fT4) levels, anthropometric measurements, and laboratory test results of these patients were analyzed. Results: 27 individuals (13.56%) presented with TSH levels above the normal level (subclinical hypothyroidism [SCH]). Their waist circumference (WC) was significantly higher than those of euthyroid individuals. Serum TSH was positively correlated with the homeostasis model assessment of insulin resistance (HOMA-IR) index, triglycerides (TG) and high-density lipoprotein cholesterol (HDL-C). Using TSH and BMI as independent variables, TSH levels were shown to be independently related to HOMA-IR (p = 0.001) and TG (p = 0.007). Among euthyroid subjects, individuals with TSH values <2.5 mIU/mL exhibited statistically significant decreases in waist-to-hip ratio, HDL-C levels, and HOMA-IR scores and a tendency toward lower WC values. Conclusion: SCH in overweight and obese adolescents appears to be associated with excess weight, especially visceral weight. In euthyroid adolescents, there appears to be a direct relationship between TSH and some CRF. In conclusion, in the present sample of overweight and obese adolescents, TSH levels appear to be associated with IR and CRF. Resumo: Objetivo: Investigar a relação entre tireotrofina sérica (TSH), resistência à insulina (RI) e fatores de risco cardiovascular (FRC) em uma amostra de adolescentes brasileiros acima do peso e obesos. Métodos: Foi realizada uma análise longitudinal retrospectiva de 190 adolescentes púberes acima do peso e obesos. Foram analisados os níveis de TSH e T4 livre (T4l), as medidas antropométricas e os resultados de exames laboratoriais desses pacientes. Resultados: 27 indivíduos (13,56%) apresentaram níveis de TSH acima do normal (hipotireoidismo subclínico (HSC)). Eles apresentaram circunferência da cintura (CC) significativamente maior que os indivíduos eutireoideos. A TSH sérica foi positivamente correlacionada ao índice do modelo de avaliação da homeostase de resistência à insulina (HOMA-IR), triglicerídeos (TG) e lipoproteína de alta densidade-colesterol (HDL-C). Usando TSH e IMC como variáveis independentes, os níveis de TSH estavam relacionados ao HOMA-IR (p = 0.001) e a TG (p = 0.007) de forma independente. Entre os pacientes eutireoideos, indivíduos com valores de TSH < 2.5 mIU/mL apresentaram reduções estatisticamente significativas na razão cintura/quadril, nos níveis de HDL-C e nos escores de HOMA-IR e tendência a menores valores de CC. Conclusão: O HSC em adolescentes acima do peso e obesos parece estar associado ao excesso de peso, principalmente de peso visceral. Em adolescentes eutireoideos, parece haver uma relação direta entre TSH e alguns FRC. Concluindo, em nossa amostra de adolescentes acima do peso e obesos, os níveis de TSH parecem estar associados a RI e FRC. Keywords: Subclinical hypothyroidism, Adolescents, Obesity, Overweight, Cardiovascular risk factors, Palavras-chave: Hipotireoidismo subclínico, Adolescentes, Obesidade, Sobrepeso, Fatores de risco cardiovascular